2019
DOI: 10.37358/rc.70.19.11.7652
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Pregnancy

Abstract: The chemical pregnancy is an early pregnancy loss occurring shortly after implantation. 50-75% of all miscarriages are considered to be chemical pregnancies. Although the pregnancy test is positive, the fetus cannot be detected on ultrasounds; it can be asymptomatic or it can have menstrual-like cramping and bleeding. There are numerous risk factors associated with miscarriage, such as: epidemiological, genetic, anatomical, endometrial, endocrine and immune factors, infections, inherited thrombophilia and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Results of the present study showed that obese pregnant women tend to have higher values of hepatic transaminases during all 3 trimesters of pregnancy compared to normal weight pregnant women, even though it was not statistically significant. However, it should be considered that AST and ALT levels were monitored dynamically, over several days; thus, it is necessary to describe the variation pattern of the AST value (23)(24)(25)(26)(27)(28)(29). It respects the cubic model with a significance value of P= 0.01, which shows that during our follow-up, the AST values tended to increase during Q2, followed by a definite decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study showed that obese pregnant women tend to have higher values of hepatic transaminases during all 3 trimesters of pregnancy compared to normal weight pregnant women, even though it was not statistically significant. However, it should be considered that AST and ALT levels were monitored dynamically, over several days; thus, it is necessary to describe the variation pattern of the AST value (23)(24)(25)(26)(27)(28)(29). It respects the cubic model with a significance value of P= 0.01, which shows that during our follow-up, the AST values tended to increase during Q2, followed by a definite decrease.…”
Section: Discussionmentioning
confidence: 99%